'Early Flower' Meets 'Petted Lion': The New Woman and New Man in Miles Franklin's 'Lost' Novel, The Net of Circumstance. Issue 3 (3rd July 2017) - Lee, Janet
Abstract: By actively contesting and challenging dominant definitions of gender and their prescribed social and familial roles, Stella Miles Franklin's 'lost' novel, The Net of Circumstance, announces itself as a realist New Woman protest novel geared to participate in critical cultural debates about the gendered practices of marriage and the inadequacies of American manhood. The author makes the case for this novel as a historically contingent text that attends to the material specificities of Franklin's negotiation with both the literary/aesthetic and socio-economic/interpersonal issues of her time. She argues for its representation of continuities between late-Victorian and modernist literary genres that include the containment of unfamiliar stories about female empowerment and the self-serving politics of pro-feminist male allies in the familiar space of courtship and marriage.